Relationships Between H2S and OT/OTR Systems in Preeclampsia - Tamara Merz; Sarah Ecker; Nicole Denoix; Oscar McCook; Stefanie Kranz; Ulrich Wachter; Edit Rottler; Thomas Papadopoulos; Christoph Fusch; Cosima Brucker; Jakob Triebel; Thomas Bertsch; et al. (Antioxidants)
Pre-eclampsia (PE) is a hypertensive pregnancy complication. Oxidative stress is hypothesized to contribute to the pathophysiology of PE. Both the hydrogen sulfide (H2S) and oxytocin (OT) systems might play a role in the pathophysiology of PE, like their antioxidant and hypotensive effects. Thus, the role of the interaction of the OT and H2S systems in the context of PE was further elucidated in the present clinical case–control study “NU-HOPE” (Nürnberg-Ulm: The role of H2S and Oxytocin Receptor in Pre-Eclampsia; ethical approval by the Landesärztekammer Bayern, file number 19033, 29 August 2019), comparing uncomplicated pregnancies, early onset PE (ePE, onset < 34 weeks gestational age) and late onset PE (lPE, onset > 34 weeks gestational age). Routine clinical data, serum H2S and homocysteine levels, and tissue protein expression, as well as nitrotyrosine formation, were determined. The main findings were (i) unchanged plasma sulfide levels, (ii) significantly elevated homocysteine levels in ePE, but not lPE, (iii) significantly elevated expression of H2S enzymes and OT receptor in the placenta in lPE, and (iv) significantly elevated nitrotyrosine formation in the lPE myometrium. Taken together, these findings suggest a role for the interaction of the endogenous H2S- and OT/OTR systems in the pathophysiology of pre-eclampsia, possibly linked to impaired antioxidant protection.